PENANGGULANGAN ABORTUS PROVOCATUS CRIMINALIS DALAM PERSPEKTIF HUKUM PIDANA - Indra Nugraha, Angga; R., Ibrahim (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013, 2013)
The rise of illegal practices abortions is highly disturbing the society, it happens because the abortion's practices have been done illegally and without a medical indication by an authorized physician, which is illegal and will endanger the safety of pregnant women and theirs fetus. In Indonesia, abortion is kind of a criminal offense and has been regulated in the Criminal Code of Indonesia. There is a lot of way to fix this crime more widespreads, such as the enforcement of criminal law and gives a maximum penalty againts the offender.
Keywords: abortus, abortus provocatus criminalis.